Antibiotic Pipeline Coordinators. (2018) - Baraldi, Enrico; Lindahl, Olof; Savic, Miloje; Findlay, David; Årdal, Christine
Abstract : The World Health Organization (WHO) has published a global priority list of antibiotic-resistant bacteria to guide research and development (R&D) of new antibiotics. Every pathogen on this list requires R&D activity, but some are more attractive for private sector investments, as evidenced by the current antibacterial pipeline. A "pipeline coordinator" is a governmental/non-profit organization that closely tracks the antibacterial pipeline and actively supports R&D across all priority pathogens employing new financing tools.